2015
DOI: 10.1149/06920.0001ecst
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Overdischarge on Large Format Lithium-Ion Cells

Abstract: Lithium-ion batteries can help enable the Navy and Marine Corps to meet their energy storage needs; however, safety is of paramount concern. Overdischarge, followed by recharge, is a failure mechanism in lithium-ion batteries that can be associated with long-term storage, poor battery module design, and internal cell defects. Overdischarge is known to cause copper dissolution, SEI layer degradation, and gas generation. By itself, overdischarge does not result in catastrophic thermal runaway; however, if a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Fuentevilla et al reported the anode potential exceeds 3.4 V for large format (>30 Ah) cell under overdischarge, the copper in the form of Cu 2+ originating from the anode's current collectors existed on the cathode 61 . In the subsequent charging, Cu 2+ will be reduced to copper atoms and plate on the surface of negative electrodes since the first Li + intercalates into carbonaceous materials.…”
Section: Inducements Of Iscmentioning
confidence: 99%
“…Fuentevilla et al reported the anode potential exceeds 3.4 V for large format (>30 Ah) cell under overdischarge, the copper in the form of Cu 2+ originating from the anode's current collectors existed on the cathode 61 . In the subsequent charging, Cu 2+ will be reduced to copper atoms and plate on the surface of negative electrodes since the first Li + intercalates into carbonaceous materials.…”
Section: Inducements Of Iscmentioning
confidence: 99%
“…During this time, apart from self-discharge, the cells might have small load requirements of the BMS and/or might even have parasitic loads. Thus, if not managed correctly, the cells might slip in time to overdischarge conditions, especially at elevated temperatures [23,32,54]. This situation might also occur in electric vehicles that are parked at low SOCs for long durations especially at high temperatures above 40 °C-they can actually overdischarge during this time (and thus significantly affect lifetime of the battery as already outlined in the previous section) [31].…”
Section: Causes Of Overdischarge In Commercial Li-ion Cellsmentioning
confidence: 98%
“…The possible factors for electrical abuse in commercialized LIBs are mainly caused by overdischarge due to inconsistencies between battery monomers. , Based on the current manufacturing of battery monomers, the factory consistency is very high. However, with the use and aging of the battery system, some of the monomers undergo a decrease in capacity and an increase in internal resistance due to the uneven working temperature during the use of the monomers, and the difference in the consistency between the monomers also follows upon battery pack aging. , This phenomenon causes some batteries to have a relatively large discharge depth under normal discharge conditions, such as instantaneous high power output of EVs and the deep discharge of grid storage batteries, and then overdischarge occurs. , Because there are series and parallel batteries in a battery system, these overdischarged batteries may not be found, posing a safety hazard for the whole battery system.…”
Section: Introductionmentioning
confidence: 99%